Preparation method and application of anisotropic nanocrystal based on self-limiting laser induction
By combining heat treatment on the Li2O-Al2O3-SiO2 glass substrate and femtosecond laser direct writing technology, a self-limiting mechanism is realized to control the growth of nanocrystals, solving the problems of low transmittance and large loss of anisotropic crystals generated by femtosecond laser direct writing, and achieving high transmittance and low loss of anisotropic nanocrystals.
Patent Information
- Application Number
- CN202411953511.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
The anisotropic crystals generated by femtosecond laser direct writing have problems with low transmittance and large losses.
By heat treatment of the Li2O-Al2O3-SiO2 glass substrate, a soft region rich in Li and a rigid region rich in Si are formed, and femtosecond laser direct writing technology is used to grow the crystal perpendicular to the laser polarization direction, realizing a self-limiting mechanism to control the growth of nanocrystals.
It effectively reduces the scattering loss of the structure, achieves a transmittance of ≥99% in the range of 400 to 1000 nm, and enhances the birefringence effect of the processing area, improving optical performance.
Smart Images

Figure CN119877105A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of laser crystallization, and more specifically, relates to a preparation method and application of self-limiting laser-induced anisotropic nanocrystals. Background Art
[0002] In the design and application of optical components, loss is a crucial parameter that directly affects the transmission efficiency of optical signals and the overall performance of the system. With the rapid development of micro-nano processing technology, reducing the size of micro-nano structures and breaking the diffraction limit have become important strategies to reduce the loss of optical components. As an advanced micro-nano processing method, femtosecond laser direct writing technology can induce the precipitation of nanocrystals in transparent media due to its unique ultra-short pulse characteristics, thereby preparing optical components with specific functions. This technology uses the nonlinear absorption characteristics of femtosecond lasers to achieve precise manipulation of the local structure and properties of materials, providing new possibilities for the innovation of optical materials.
[0003] In recent years, most structures induced by femtosecond lasers have been isotropic, which, to a certain extent, limits their wide applicability in specific applications. In addition, although femtosecond laser direct writing technology has also made significant progress in realizing anisotropic structures, such as nano-gratings, the periodic fluctuations of nano-grating structures cause large scattering in the ultraviolet and visible light regions. In addition, the size is close to the wavelength, which makes the optical components produced have low transmittance, greatly limiting their application in the optical field. Summary of the invention
[0004] In view of the defects of the related art, the purpose of the present invention is to provide a preparation method and application based on self-limiting laser-induced anisotropic nanocrystals, aiming to solve the problems of low transmittance and large loss of anisotropic crystals generated by femtosecond laser direct writing.
[0005] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing self-limiting laser-induced anisotropic nanocrystals, comprising:
[0006] S1. heat-treating a Li2O-Al2O3-SiO2 glass substrate so that the Li2O-Al2O3-SiO2 glass substrate undergoes phase separation to form a soft region rich in Li and a rigid region rich in Si; at least one isotropic crystal nucleus or a crystal with a size less than 30 nm is generated in the soft region;
[0007] S2. Using femtosecond laser direct writing on the phase-separated Li2O-Al2O3-SiO2 glass substrate to make the crystal nuclei or nanocrystals grow perpendicular to the laser polarization direction to form anisotropic nanocrystals.
[0008] Optionally, before S1, the method further includes: determining the heat treatment temperature of the Li2O-Al2O3-SiO2 glass substrate by using differential scanning calorimetry.
[0009] Optionally, the composition of the Li2O-Al2O3-SiO2 glass substrate is SiO2:Li2O:Al2O3:B2O3:Na2O:ZrO2:P2O5, wherein the molar ratio of each substance is 70.09:21.42:4.27:0.15:1.48:1.75:0.83.
[0010] Optionally, the polarization state of the femtosecond laser used in the femtosecond laser direct writing is linear polarization, the pulse width of the femtosecond laser is 800fs, the scanning speed of the femtosecond laser is 0.05mm / s, the single pulse energy of the femtosecond laser does not exceed 2000nJ, and the repetition frequency range is 50-300kHz.
[0011] Optionally, the size of the anisotropic nanocrystals along the long axis direction ranges from 30 to 90 nm.
[0012] Optionally, the transmittance of the anisotropic nanocrystals at a preset target wavelength is ≥ 99.0%, and the preset target wavelength is 400-1000 nm.
[0013] In a second aspect, the present invention further provides an anisotropic nanocrystal prepared by the preparation method described in any one of the first aspects.
[0014] In a third aspect, the present invention further provides a transparent optical element, comprising a Li2O-Al2O3-SiO2 glass substrate and anisotropic nanocrystals as described in the second aspect located in the Li2O-Al2O3-SiO2 glass substrate.
[0015] In a fourth aspect, the present invention further provides an optical storage system, wherein the storage voxels are the anisotropic nanocrystals as described in the second aspect.
[0016] In a fifth aspect, the present invention further provides an optical storage method, which is applied to the optical storage system as described in the fourth aspect, and uses at least one of the spatial three-dimensional position of the anisotropic nanocrystals, the slow axis angle of the overall structure, and the delay value to store information.
[0017] Compared with the prior art, the above technical solution conceived by the present invention can achieve the following beneficial effects:
[0018] 1. The present invention provides a preparation method based on self-limiting laser-induced anisotropic nanocrystals. Process I produces a Si-rich rigid region and a Li-rich soft region in a Li2O-Al2O3-SiO2 glass substrate by heat treatment. Among them, the existence of the rigid region mainly inhibits the growth of nanocrystals. In process II, femtosecond laser direct writing allows the crystal to grow perpendicular to the laser polarization direction, and the migration of some ions enhances the degree of polymerization in the rigid region. Once the nanocrystal exceeds the phase boundary, its growth will be inhibited by the rigid region. Therefore, the growth of the nanocrystal will slow down and will not exceed the soft region too much. This self-limiting mechanism limits the size of the anisotropic nanocrystals along the long axis to a range of 30 to 90 nm. According to the Rayleigh scattering theory, the scattering intensity is proportional to the sixth power of the size of the nanostructure, so this method effectively reduces the scattering loss of the structure. In addition, a transmittance of ≥99% is achieved within the preset target wavelength range of 400 to 1000 nm.
[0019] 2. The present invention provides a method for preparing anisotropic nanocrystals based on self-limiting laser-induced anisotropic nanocrystals. In process I of the method, two regions with opposite functions are generated in Li2O-Al2O3-SiO2 glass through a heat treatment process. The phase boundary between the two regions has a lower interface free energy, and the sharp concentration gradient promotes ion diffusion, thereby promoting nucleation, resulting in more nucleation or crystallization sites in the Li2O-Al2O3-SiO2 glass substrate. In the subsequent stage of process II, the near-field anisotropic characteristics of the interaction between light and matter are utilized to make the crystal nuclei or nanocrystals formed in the process I stage continue to grow into anisotropic nanocrystals. This strategy effectively enhances the birefringence effect of the processing area. Specifically, under the same laser irradiation conditions, compared with traditional femtosecond laser direct writing, the volume fraction of anisotropic nanocrystals obtained by the present invention increases by 0.016, the delay value of the structure increases by 10nm, reaching 360nm / mm, and the percentage increases by 140%.
[0020] 3. The present invention provides a method for preparing self-limiting laser-induced anisotropic nanocrystals. In actual processing, the heat accumulation effect of the laser writing process can be controlled by adjusting the laser energy and repetition frequency. Due to the existence of the rigid region, even when the laser repetition rate or single pulse energy is continuously increased, the size of the anisotropic nanocrystals can be well controlled within the low scattering range. Compared with the traditional femtosecond laser direct writing technology, this method provides a larger parameter processing window, and its range has increased by about 83%.
[0021] 4. The present invention provides a preparation method based on self-limiting laser-induced anisotropic nanocrystals, which makes the structure have high transparency and good birefringence properties. Based on the present invention, the obtained structure with high transparency and good birefringence properties can be used to make various transparent optical elements and multidimensional optical storage. Taking multidimensional optical storage as an example, in addition to the three common dimensions of three-dimensional spatial position, the two dimensions of the slow axis angle and delay value of the overall structure can also be used for storage. The present invention uses the slow axis angle as the fourth dimension to achieve highly transparent 1000-layer multidimensional optical storage in a bulk Li2O-Al2O3-SiO2 glass substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is the DSC curve of the original Li2O-Al2O3-SiO2 glass;
[0023] Figure 2 Schematic diagram of light transmission of three nanostructures in glass substrate;
[0024] Figure 3 It is based on the precipitation process of self-limited laser-induced anisotropic nanocrystals;
[0025] Figure 4 The scanning electron microscope images are those without heat treatment and after being modified by femtosecond laser with different repetition rates;
[0026] Figure 5 The relationship between the increase in retardation value and the volume fraction of nanocrystals of laser-modified glass without heat treatment and laser-modified glass after heat treatment and the change of laser parameters;
[0027] Figure 6 The scanning electron microscope images and transmittance spectra of heat-treated glass and its modified by femtosecond laser with different repetition frequencies;
[0028] Figure 7 For the preparation of geometric phase lenses and prisms;
[0029] Figure 8 A polarization vector beam converter for a target wavelength of 515 nm;
[0030] Fig. 9 This is a processing demonstration diagram of 1000 layers of transparent multi-dimensional optical storage. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] The contents involved in the above embodiment are described below in conjunction with a preferred embodiment.
[0033] The glass used in the following implementation examples is Li2O-Al2O3-SiO2 glass. The entire femtosecond laser system consists of a femtosecond laser, an energy control module, a polarization control module, an XYZ three-axis translation stage, and an imaging module. The control linkage of each module is controlled by the C# language coding language. The femtosecond laser used in the system is a frequency-doubled femtosecond laser system (FemtoYL-20). The laser pulse emitted by the system has a pulse width of 300 to 2000fs, a central wavelength of 515nm, a spot diameter of 3mm, and a pulse width of 800fs used in the example. In the energy control module, the laser pulse energy is continuously controlled by adjusting the relative optical axis angles of the achromatic zero-order half-wave plate (LBTEK, AHWP10-VIS) and the Glen-Tiger polarization cubic crystal (LBTEK, GLP10-A). In the polarization control module, the polarization angle of the incident beam is controlled by controlling the achromatic zero-order half-wave plate (LBTEK, AHWP10-VIS). The light beam was incident perpendicularly to the glass surface through an air objective lens with a numerical aperture of 0.25. The optical image was taken using an optical microscope, model Olympus BX51; the birefringence image was obtained using a birefringence measurement system (PolScope) installed on BX51.
[0034] Embodiment 1
[0035] The present invention provides a method for preparing self-limiting laser-induced anisotropic nanocrystals, comprising:
[0036] S1. heat-treating a Li2O-Al2O3-SiO2 glass substrate so that the Li2O-Al2O3-SiO2 glass substrate undergoes phase separation to form a soft region rich in Li and a rigid region rich in Si; at least one isotropic crystal nucleus or a crystal with a size less than 30 nm is generated in the soft region;
[0037] S2. Using femtosecond laser direct writing on the phase-separated Li2O-Al2O3-SiO2 glass substrate to make the crystal nuclei or nanocrystals grow in a direction perpendicular to the laser polarization direction.
[0038] Optionally, before S1, the method further includes: determining the heat treatment temperature of the Li2O-Al2O3-SiO2 glass substrate by using differential scanning calorimetry.
[0039] In a specific embodiment, the steps include:
[0040] (1) Heat treatment (process I)
[0041] The preheating temperature was determined by differential scanning calorimetry (DSC). According to the DSC curve, four exothermic peaks were obtained, including lithium metasilicate (Li2Si2O3), lithium disilicate (Li2Si2O5), quartz (SiO2), petalite (LiAlSi4O 10 ) and spodumene (LiAlSi2O6). The temperature of the first crystallization peak is about 658°C, and the temperature of the start of crystallization is about 620°C. Therefore, a temperature range of 540°C to 600°C is selected, and a box-type heat treatment furnace is used to preheat the Li2O-Al2O3-SiO2 glass to produce phase separation and crystal nuclei in process I. In this embodiment, the composition of the selected Li2O-Al2O3-SiO2 glass substrate is SiO2:Li2O:Al2O3:B2O3:Na2O:ZrO2:P2O5, and the molar ratio of each substance is 70.09:21.42:4.27:0.15:1.48:1.75:0.83. Among them, a small amount of P2O5 is used to promote nucleation.
[0042] Figure 1 The DSC curve of the original Li2O-Al2O3-SiO2 glass. According to the DSC curve, four exothermic peaks were obtained, including lithium metasilicate (Li2Si2O3), lithium disilicate (Li2Si2O5), quartz (SiO2), petalite (LiAlSi4O 10 ) and spodumene (LiAlSi2O6). The temperature of the first crystallization peak is about 658°C, and the temperature of the start of crystallization is about 620°C. Therefore, a temperature range of 540°C to 600°C is selected to preheat the Li2O-Al2O3-SiO2 glass in a box-type heat treatment furnace to produce phase separation and crystal nuclei in process I.
[0043] (2) Low-loss anisotropic nanocrystal precipitation (process II)
[0044] In this embodiment, optionally, the polarization state of the femtosecond laser used in the femtosecond laser direct writing is linear polarization, the pulse width of the femtosecond laser is 800fs, the scanning speed of the femtosecond laser is 0.05mm / s, the single pulse energy of the femtosecond laser does not exceed 2000nJ, and the repetition frequency range is 50-300kHz.
[0045] The linearly polarized femtosecond laser passes through a 0.25NA objective lens and is incident vertically onto the heat-treated Li2O-Al2O3-SiO2 glass surface 100 μm below the surface for processing. The scanning speed is 0.05 mm / s, the pulse width is 800 fs, and the surface is processed by raster scanning with a line spacing of 1 μm. Furthermore, the laser used in this embodiment has a single pulse energy range of 100 to 2000 nJ and a repetition frequency range of 100 to 300 kHz. Specifically, in this embodiment, the selected single pulse energies are 300 nJ, 400 nJ, and 500 nJ, and the repetition frequencies are 150 kHz, 200 kHz, and 250 kHz.
[0046] (3) Generation of anisotropic nanocrystals in specific directions
[0047] By adopting the above-mentioned heat treatment conditions and laser parameters, a half-wave plate is used to modulate the polarization direction of the incident femtosecond laser, so that nanocrystals in different directions can be precipitated by adjusting the polarization direction of the laser, wherein the long axis direction of the nanocrystal is always perpendicular to the polarization direction of the laser. In this embodiment, the polarization direction is a vertical direction (perpendicular to the scanning direction), and the change in the slow axis direction of the anisotropic nanocrystal in the implementation application is also based on this control. Among them, when the anisotropic crystal grows, once it exceeds the phase boundary, its growth will be inhibited by the rigid region.
[0048] Figure 2 Schematic diagram of light transmission of three types of nanostructures in a glass substrate: an isotropic structure in the Rayleigh range (left), an anisotropic structure at the wavelength scale (middle), and an anisotropic nanostructure in the Rayleigh scattering range (right).
[0049] Figure 3 The process is based on the precipitation of self-limited laser-induced anisotropic nanocrystals, which is divided into two stages; the first stage involves heat treatment to produce two functionally opposite regions (the Si-rich phase barrier region and the Li-rich phase soft region); the second stage promotes the anisotropic growth of nanocrystals by direct writing with a femtosecond laser, during which the crystals grow along the direction perpendicular to the laser polarization, while the continuous migration of ions increases the degree of polymerization of the rigid region. When the growth of the nanocrystal exceeds the phase boundary, its growth is inhibited by the rigid region.
[0050] Optionally, the size of the anisotropic nanocrystals along the long axis direction ranges from 30 to 90 nm.
[0051] Optionally, the transmittance of the anisotropic nanocrystals at a preset target wavelength is ≥ 99.0%, and the preset target wavelength is 400-1000 nm.
[0052] In this embodiment, two different functional areas are produced after heat treatment of the Li2O-Al2O3-SiO2 glass substrate, and its self-limiting mechanism limits the anisotropic nanocrystals to a range of 30 to 90 nm along the long axis. According to the Rayleigh scattering theory, the scattering intensity is proportional to the sixth power of the size of the nanostructure, so this method effectively reduces the scattering loss of the structure. A transmittance of ≥99% is achieved within the preset target wavelength range of 400 to 1000 nm. According to the above method, anisotropic nanocrystals are prepared, which effectively enhances the birefringence effect of the processing area, increases the volume fraction of the anisotropic nanocrystals by 0.016, and increases the delay value of the structure by 10 nm to 360 nm / mm, and the percentage increases by 140%. The problem of low transmittance and large loss of anisotropic crystals generated by femtosecond laser direct writing is solved. Anisotropic crystals with high transmittance and low loss are achieved.
[0053] Furthermore, in actual processing, the heat accumulation effect of the laser writing process can be controlled by adjusting the laser energy and repetition frequency. Due to the existence of the rigid region, even when the laser repetition rate or single pulse energy is continuously increased, the size of the anisotropic nanocrystals can be well controlled within the low scattering range. Compared with traditional femtosecond laser direct writing technology, this method provides a larger parameter processing window, with a range increased by about 83%.
[0054] Comparative Example: Existing High-Loss Anisotropic Nanocrystal Precipitation
[0055] Linear polarized femtosecond laser passes through a 0.25NA objective lens and is incident vertically on the Li2O-Al2O3-SiO2 glass 100 μm below the surface for processing. The scanning speed is 0.05 mm / s, the pulse width is 800 fs, and the surface is processed by raster scanning with a line spacing of 1 μm. The difference from the embodiment is that the Li2O-Al2O3-SiO2 glass at this time is not processed by process I. For the original glass that has not been heat-treated, as the repetition rate or the single pulse energy increases, the size of the anisotropic nanocrystals gradually increases and is not limited to more than 200 nm. Figure 4 As shown, Figure 4 Scanning electron microscope images of the sample before heat treatment and after femtosecond laser modification with different repetition rates.
[0056] Figure 5 The relationship between the increase in retardation value and the volume fraction of nanocrystals of laser-modified glass without heat treatment and laser-modified glass after heat treatment as a function of laser parameters. Figure 5(a) shows the delay increase and range of laser-induced nanostructures with different pulse densities and pulse energies (the left and right dashed lines represent the boundary between low-scattering and high-scattering structures of laser-modified glass without heat treatment and laser-modified glass with heat treatment, respectively). Under the same femtosecond laser processing conditions, compared with the glass without heat treatment, the delay value of the nanostructure under the optimal heat treatment condition increased by 10nm to 360nm / mm, and the percentage increased by 140%; Figure 5 (b) is a graph showing the relationship between the volume fraction of nanocrystals and pulse energy under two processing methods. The volume fraction of the heat-treated glass increased by 0.016, which is 80% higher than the volume fraction of the untreated glass.
[0057] The size of anisotropic nanocrystals formed by unheat-treated Li2O-Al2O3-SiO2 glass under femtosecond laser processing increases with the increase of single pulse energy or repetition frequency, exceeding 200nm, forming a high-loss nanostructure. In comparison, under the same conditions, the size of anisotropic nanostructures of preheat-treated glass is much smaller than the wavelength, belonging to a low-scattering structure, and exhibiting stronger birefringence characteristics, showing better optical properties.
[0058] Embodiment 2
[0059] The same parameters as those in Example 1 (1) during the heat treatment process were used, and the parameters in (2) the process of precipitation of low-loss anisotropic nanocrystals were changed; specifically, a linearly polarized femtosecond laser was incident vertically through a 0.25NA objective lens onto the heat-treated Li2O-Al2O3-SiO2 glass surface at 100 μm below the surface for processing, with a scanning speed of 0.05 mm / s, a pulse width of 800 fs, and a line spacing of 1 μm using a grating scanning method to process the surface. The laser used in this example has a single pulse energy of 300 nJ, 400 nJ, and 500 nJ, and a repetition frequency of 150 kHz, 200 kHz, and 250 kHz. The parameters in the process of generating anisotropic nanocrystals in a specific direction (3) were kept unchanged, and the polarization direction was the vertical direction.
[0060] In another embodiment, the single pulse energy of the laser used is 400 nJ and the repetition frequency is 150 kHz. The parameters in the process of generating (3) anisotropic nanocrystals in a specific direction are kept unchanged. The direction of the slow axis of birefringence is always perpendicular to the polarization direction.
[0061] Figure 6 The scanning electron microscope images and transmittance spectra of heat-treated glass and its modified by femtosecond laser with different repetition rates. Figure 6(a) is the SEM image of heat-treated glass and heat-treated laser-modified glass at different repetition frequencies of 150kHz, 200kHz and 250kHz, corresponding to two examples in Example 1 and this embodiment, respectively. As the laser repetition frequency increases, the size of the anisotropic nanocrystals is limited to less than 100nm; Figure 6 Figure b shows the experimental and simulated transmittance spectra. The size of the nanocrystal is limited to 30-90nm (along the long axis), and the transmittance is greater than 99% in the wavelength range of 400nm to 1000nm. When the long axis of the nanocrystal is set to 40nm, the simulated structure based on Rayleigh scattering theory is consistent with the experimental results.
[0062] Embodiment 3
[0063] The same parameters as those in (1) the heat treatment process in Example 1 and the same parameters as those in (2) the precipitation process of low-loss anisotropic nanocrystals are used; specifically, a linearly polarized femtosecond laser is incident vertically through a 0.25NA objective lens to 100 μm below the surface of the heat-treated Li2O-Al2O3-SiO2 glass for processing, with a scanning speed of 0.05 mm / s, a pulse width of 800 fs, and a line spacing of 1 μm using a grating scanning method to process the surface. The laser used in this example has a single pulse energy of 400 nJ and a repetition frequency of 150 kHz. By changing the parameters in the process of generating anisotropic nanocrystals in a specific direction (3), the precipitation of nanocrystals in different directions can be achieved by adjusting the polarization direction of the laser, wherein the long axis direction of the nanocrystal is always perpendicular to the polarization direction of the laser.
[0064] Embodiment 4
[0065] The present invention also provides an anisotropic nanocrystal, which is prepared by the above-mentioned preparation method based on self-limiting laser induced anisotropic nanocrystal.
[0066] Embodiment 5
[0067] The present invention also provides a transparent optical element, comprising a Li2O-Al2O3-SiO2 glass substrate and anisotropic nanocrystals according to the fourth embodiment located in the Li2O-Al2O3-SiO2 glass substrate.
[0068] The transparent optical element includes a transparent geometric lens, a geometric prism and a vector deflection converter
[0069] Example: Making a transparent geometric lens
[0070] In this embodiment, 12 layers are processed to make the delay value reach about 255nm (half of the target wavelength of 515nm), and the specific operations are as follows:
[0071] The femtosecond laser processes different layers from bottom to top, with a layer spacing of 20μm. The processing parameters of each layer are the same, and they are absolutely overlapped from the direction of laser incidence. The processing parameters of each layer are as follows: the objective lens is 0.25NA, the laser scanning speed is 0.05mm / s, the laser pulse width is 800fs, the single pulse energy is 400nJ, the repetition frequency is 150kHz, and the slow axis direction is parabolic. The surface is processed by grating scanning with a line spacing of 1μm, and finally a geometric phase lens with a diameter of 2mm and a thickness of 250μm is formed. When the vertical incident circular deflected light is directed to the processed structure, the left-right rotation of the incident circularly polarized light is changed, and the focusing and defocusing of the outgoing light can be achieved.
[0072] Example: Making a transparent geometric prism
[0073] In this embodiment, 12 layers are processed to make the delay value reach about 255nm (half of the target wavelength of 515nm), and the specific operations are as follows:
[0074] The femtosecond laser processes different layers from bottom to top, with a layer spacing of 20μm. The processing parameters of each layer are the same, and they are absolutely overlapped from the direction of laser incidence. The processing parameters of each layer are as follows: the objective lens is 0.25NA, the laser scanning speed is 0.05mm / s, the laser pulse width is 800fs, the single pulse energy is 400nJ, the repetition frequency is 150kHz, and the slow axis direction is gradiently distributed along the horizontal direction. The surface is processed by grating scanning with a line spacing of 1μm, and finally a geometric phase prism with a radius of 1mm (the radius can be adjusted arbitrarily) is formed. When the vertical incident circular deflected light is incident on the processed structure, the left-right rotation of the incident circularly polarized light is changed, and the direction of the outgoing light can be changed.
[0075] Figure 7 For the preparation of geometric phase lenses and prisms. Figure 7 (a) is the birefringence image of the geometric phase lens, and its slow axis direction is parabolic distribution. By changing the left-right rotation of the incident circularly polarized light, the focus and defocus of the outgoing light can be changed ( Figure 7 (b)); Figure 7 The middle (c) figure shows the birefringence image of the geometric phase prism. Its slow axis direction is distributed along the horizontal gradient. By changing the left-right rotation direction of the incident circularly polarized light, the direction of the outgoing light can be changed ( Figure 7 (d)).
[0076] Example: Fabrication of a vector deflection converter with a target wavelength of 515 nm
[0077] In this embodiment, 6 layers are processed to achieve a delay value of about 126 nm (a quarter of the target wavelength of 515 nm). The specific operations are as follows:
[0078] The femtosecond laser processes different layers from bottom to top, with a layer spacing of 20μm. The processing parameters of each layer are the same, and they are absolutely overlapped from the direction of laser incidence. The processing parameters of each layer are as follows: the objective lens is 0.25NA, the laser scanning speed is 0.05mm / s, the laser pulse width is 800fs, the single pulse energy is 400nJ, the repetition frequency is 150kHz, and the slow axis direction is processed from 0° to 360° at intervals of 20° to produce 18 sectors. The sector surface is processed using a grating scanning method with a line spacing of 1μm, and finally a vortex beam converter with a radius of 1mm (the length can be adjusted arbitrarily) is formed. When the vertical incident circularly deflected light is incident on the processed structure, the left-right handedness of the incident circularly polarized light is changed, and radial and azimuthal polarized light are generated respectively.
[0079] Figure 8 Polarization vector beam converter for target wavelength 515nm. Figure 8 (a) is an optical image of a polarization vector beam converter; Figure 8 (b) is a birefringent image (processing 6 layers to make the delay value about 126nm). When the left-right rotation of the incident circularly polarized light is changed, radial and azimuthal polarized light will be generated respectively ( Figure 8 (c)).
[0080] Embodiment 6
[0081] The present invention also provides an optical storage system, wherein the storage medium is the anisotropic nanocrystal as described in the fourth embodiment.
[0082] Embodiment 7
[0083] The present invention also provides an optical storage method, which is applied to the optical storage system as described in Example 6, and uses at least one of the spatial three-dimensional position of the anisotropic nanocrystals, the slow axis angle of the overall structure, and the delay value to store information.
[0084] Example: Multidimensional optical storage demonstration
[0085] The specific operation is as follows: anisotropic nanocrystal voxel arrays are recorded point by point, 3000 pulses are used for each voxel data, the objective lens is 0.25NA, the laser pulse width is 800fs, and the single pulse energy is 300nJ.
[0086] Fig. 9 This is a processing demonstration diagram of 1000 layers of transparent multi-dimensional optical storage. Fig. 9 (a) is an optical image of multi-dimensional storage processing; Fig. 9 (b) is the birefringence image of layer 1, and part of its data is encoded as follows: Fig. 9 As shown in (d), in order to obtain an accurate and clear birefringence image, the Jones matrix algorithm is used to remove the interference of background noise on the birefringence signal; Fig. 9(c) shows the reading accuracy of the 1st, 400th, 700th and 1000th layers (a total of 1600 data points), and its value reaches 99.75%.
[0087] In order to demonstrate transparent multi-dimensional optical storage, "The Old Man and the Sea" was encoded, and the digital information was encrypted into four states of the slow axis direction, representing two data for each voxel, with the slow axis as the fourth dimension. A total of 1000 layers were processed in the example, with a layer spacing of 10μm. In order to obtain accurate and clear birefringence images, the Jones matrix algorithm was used to remove the interference of background noise on the birefringence signal. The accuracy of 1, 400, 700 and 1000 layers (a total of 1600 data points) was read, and the value reached 99.75%.
[0088] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing self-limiting laser-induced anisotropic nanocrystals, characterized in that: include: S1. heat-treating a Li2O-Al2O3-SiO2 glass substrate so that the Li2O-Al2O3-SiO2 glass substrate undergoes phase separation to form a soft region rich in Li and a rigid region rich in Si; at least one isotropic crystal nucleus or a crystal with a size less than 30 nm is generated in the soft region; S2. Using femtosecond laser direct writing on the phase-separated Li2O-Al2O3-SiO2 glass substrate to make the crystal nuclei or nanocrystals grow perpendicular to the laser polarization direction to form anisotropic nanocrystals.
2. The preparation method according to claim 1, characterized in that Before S1, the method further includes: using differential scanning calorimetry to determine the heat treatment temperature of the Li2O-Al2O3-SiO2 glass substrate.
3. The preparation method according to claim 1, characterized in that: The composition of the Li2O-Al2O3-SiO2 glass substrate is SiO2:Li2O:Al2O3:B2O3:Na2O:ZrO2:P2O5, wherein the molar ratio of each substance is 70.09:21.42:4.27:0.15:1.48:1.75:0.
83.
4. The preparation method according to claim 1, characterized in that: The polarization state of the femtosecond laser used in the femtosecond laser direct writing is linear polarization, the pulse width of the femtosecond laser is 800fs, the scanning speed of the femtosecond laser is 0.05mm / s, the single pulse energy of the femtosecond laser does not exceed 2000nJ, and the repetition frequency ranges from 50-300kHz.
5. The preparation method according to claim 1, characterized in that: The size of the anisotropic nanocrystal along the long axis direction ranges from 30 to 90 nm.
6. The preparation method according to claim 1, characterized in that: The transmittance of the anisotropic nanocrystal at a preset target wavelength is ≥99.0%, and the preset target wavelength is 400-1000 nm.
7. An anisotropic nanocrystal, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 6.
8. A transparent optical element, characterized in that: The invention comprises a Li2O-Al2O3-SiO2 glass substrate and the anisotropic nanocrystals as claimed in claim 7 located in the Li2O-Al2O3-SiO2 glass substrate.
9. An optical storage system, characterized in that: The storage voxel is the anisotropic nanocrystal as claimed in claim 7.
10. An optical storage method, characterized in that: Applied to the optical storage system as claimed in claim 9, information is stored using at least one of the spatial three-dimensional position of the anisotropic nanocrystal, the slow axis angle of the overall structure, and the delay value.